Quantifying stranding risk for fossil fuel assets and implications for renewable energy investment: A review of the literature. (December 2019) - Curtin, J.; McInerney, C.; Ó Gallachóir, B.; Hickey, C.; Deane, P.; Deeney, P.
Abstract: Investment in sustainable and renewable technologies must be doubled if globally agreed climate targets are to be met. The ways in which stranded asset risk from climate change could impact the risk-return preferences and capital allocation decisions is therefore receiving increased attention. We develop an analytical framework to systematically review the literature on stranded asset risk across the investment chain: for physical assets, securities, investment portfolios, the creditworthiness of financial institutions, and the stability of the financial system. We find that there has been a strong focus on evaluating stranding risk for illiquid assets at the earlier points in the investment chain: fossil fuel reserves and the energy generation sector. These studies identify stranding risk for high cost or carbon-intensive reserves and for energy generation technologies dependent on these resources, in particular coal. There is also some evidence that owners of financial assets could also be exposed to stranding risk because the valuations of coal, oil and gas companies could be overstated, particularly for undiversified companies with high capital exposure to carbon-intensive resources. Moving along the investment chain, there are fewer studies quantifying risks for the creditworthiness of counterparties, asset portfolio managers, financial institutions and the stability of the financial system. While there is some evidence that stranding risk may be an issue for financial institutions and investment portfolios, other studies find that risks to more liquid assets are less acute and can be managed by diversification strategies. These are areas meriting further research. Graphical abstract: Image 1 Highlights: Stranded asset risk from climate mitigation affects capital allocation decisions. Evaluating risks at earlier points in the investment chain has been the main focus. High cost and carbon-intensive fossil fuel reserves are highly exposed. Stranding risk could also affect financial institutions and investment portfolios. Further research is needed to assess risks at later points in the investment chain.